The School for Democracy: Co-operation and the Authoritarian State in 1930s Estonia - Liisi Veski (Acta Historica Tallinnensia, 2024)
This article explores the complex relationship between the co-operative movement and the authoritarian state in Estonia from 1934 to 1940. It analyses the dynamics, connections, and tensions that emerged between the co-operative movement â traditionally seen as a grassroots initiative â and the organic-statist, centralising corporatist model promoted by authoritarian regimes across Europe during the interwar period. To begin, the article provides a comprehensive overview of the general shifts in the autonomy of the co-operative movement in Estonia following the introduction of authoritarian rule. Additionally, it analyses the role of the co-operative movement as a potential platform for democratic opposition during the authoritarian period of the 1930s. Finally, the article highlights the fluidity of boundaries between the co-operative from-below and organic-statist corporative models, exemplified through a case study of the Chamber of Co-operative Societies launched in the mid-1930s, an initiative originating from co-operative activists themselves.